Analisis Tingkat Pendapatan dan Kesejahteraan Pelaku Usaha di Kawasan Wisata Pantai Pasir Putih Kabupaten Manokwari - Ketysia Imelda Tewernusa; Rumas Alma Yap; Ali Akbar Rafsanjani (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2018)
The purpose of this study was to analyze the level of income and welfare of business people who have businesses in white sand beach tourism areas. Data obtained from the results of interviews, observations and literature that has been carried out on business people. The results obtained show that the average income of traders from businesses in tourist attractions in Pasir Putih Beach is IDR 41,644,000 per year. Annual per capita income of Rp. 17,196,181 and included in the category of not poor with a score of 4 and per capita expenditure per year Rp. 6,877,790, in this amount categorized as not poor with a score of 4. It is known that the average score of businesses in the tourism area White Sand Beach is 30 which are categorized as high for the level of welfare.